Correlates to Human Papillomavirus Vaccination Status and Willingness to Vaccinate in Low‐Income Philadelphia High School Students. (August 2015) - Bass, Sarah B.; Leader, Amy; Shwarz, Michelle; Greener, Judith; Patterson, Freda
ABSTRACT BACKGROUND Little is known about the correlates of human papillomavirus (HPV) vaccination or willingness to be vaccinated in urban, minority adolescents. METHODS Using responses to the 2013 Youth Risk Behavior Survey in Philadelphia, a random sample of high schools provided weighted data representing 20, 941 9th to 12th graders. Stratified by either having had or willingness to have the vaccine, bivariate analysis with sexual behavior, preventive health behaviors, mental health, substance use, and demographic characteristics were examined and then multivariable regression models were developed to estimate significant correlates. RESULTS Respondents were 52.3% female, 84.4% non‐White, and 65.9% ≥16 years; 43% reported having had the HPV vaccine, and of those not vaccinated, 66% reported willingness to be vaccinated. Logistic regression models indicate that females (odds ratio [OR] = 3.12, p < .01) and those reporting human immunodeficiency virus (HIV) testing (OR = 2.10, p < .01) were more likely to be vaccinated. Those reporting condom use during last intercourse (OR = 0.40; p = .05) and current marijuana use (OR = 0.37; p = .03) were less likely to indicate willingness to be vaccinated. CONCLUSIONS Important areas for intervention include addressing misconceptions or feelings of "immunity, " especially for those using condoms. Understanding the correlation between HIV testing and HPV vaccination is also an important intervention opportunity for schools hoping to increase adolescent vaccination rates.